E-083 Acute Stroke Intervention for Large Vessel Occlusion with Combined Stent Retriever and Suction Thrombectomy (Solumbra Technique): A Retrospective Analysis of 85 Patients. (29th July 2016) - Wong, J; Telischak, N; Heit, J; Moraff, A; Dodd, R; Do, H; Marks, M
Abstract : Introduction: The superiority of mechanical thrombectomy over medical management has been established in recent randomized controlled trials, however, controversy remains over the most effective and safest technique for clot retrieval. Mechanical thrombectomy for large vessel occlusion (LVO) can be performed through aspiration alone with the ADAPT technique, or combined stent retriever with aspiration either in the cervical vasculature using a proximal balloon guide, or directly at the clot face with an intermediate catheter, the so-called "Solumbra" technique. The purpose of this study was to evaluate the efficacy and safety of the Solumbra technique at our institution. Methods: A retrospective chart review was conducted of all patients undergoing endovascular stroke treatment for LVO using the Solumbra technique between January 2014 and March 2016. The Solumbra technique consisted of deployment of a stent retriever (Solitaire, Trevo or Mindframe) distal to the clot with an intermediate catheter (5 Max Ace, Ace 64 or SOFIA) at the clot face. Patient demographic data, stroke presentation, treatment details, and complications were recorded. The primary outcome was successful TICI 2 B/3 reperfusion and the number of passes for revascularization. Secondary outcome measures were complication rates, including symptomatic intracranial hemorrhage (PH2 hemorrhage with a NIHSS increase >4) and mRS ≤ 2 on discharge. Embolization into new territory was based on new post-procedure MRI DWI lesions. Results: The Solumbra technique was performed for LVO in 85 patients (37 male, 48 female) with a mean age of 71.4 years (range 28–93). The mean NIHSS on presentation was 14 (IQR 10–19), and IV tPA was administered in 65% of patients. Vessel occlusion was located predominantly in the anterior circulation in the ICA terminus (n = 12, 14%), M1 (n = 51, 60%) and M2 (n = 16, 19%) segments, with Basilar occlusion occurring in 7 patients (8%). Successful reperfusion (TICI 2 B/3) was achieved in 88% of patients, consisting of TICI 3 in 38 patients (45%). The mean number of passes for revascularization was 1.9 (SD 1.3) and time from access to revascularization was 52.7 minutes (95% CI 45.3–60.1). Mean NIHSS on discharge was 7 (IQR 2–12) with good functional outcome (mRS ≤ 2) present in 44% of patients, and mortality (mRS = 6) rate of 12%. Complications included parenchymal hemorrhagic transformation (18%), symptomatic intracranial hemorrhage (4.7%) and emboli in new territory based on new MRI lesions (7%). Conclusion: The Solumbra technique compares favourably to other thrombectomy techniques used for acute stroke intervention. It achieved a TICI 2 B/3 reperfusion in 88% of patients, with an average number of 1.9 passes. Good functional outcome was achieved in 44% of patients on discharge, with a symptomatic intracranial hemorrhage rate of 4.7%. Disclosures: J. Wong: None. N. Telischak: None. J. Heit: None. A. Moraff: None. R. Dodd: None. H. Do: None. M. Marks: None.